A Design Management Framework for the Fashion Industry - Cláudia de Souza Libanio; Fernando Goncalves Amaral (BBR: Brazilian Business Review)
Organizations have been demonstrating an interest to invest in design, perceiving it as a strategic element to obtain competitive advantage. Design must become an integral part of the corporate objectives, permeating all levels of corporate activities. For this reason, this paper aims to propose a framework based on concepts of competences by checking and assessing their applicability in design management in the apparel industry. This study included conducting a literature research, through the development of a systematic literature review as well as an exploratory study with a qualitative approach, through the use of in-depth interviews. This proposed framework was then exposed to the evaluation of specialists. After this assessment, adjustments were suggested, resulting in the final proposal of the framework for training and integration of individuals and teams in design management for companies in the apparel industry, supported by the concepts of competence. This framework identifies phases and design professional activities that are crucial for the occurrence of design management and are related to product development process, articulating the organizational strategies and the market research. By using the framework, we expect design to affect all organization levels, being present in the stages of the development process in a collection.